Could a Two-Staged Repair Be the Solution to the Dilemma of Repair Timing for Severe Congenital Diaphragmatic Hernia Requiring Extracorporeal Membrane Oxygenation? - Akiko Yokoi (MDPI AG, 2024)
Purpose of review: Congenital diaphragmatic hernia (CDH) remains a significant challenge, particularly in severe cases with persistent pulmonary hypertension (PPHN) and hypoplastic lungs and heart. For patients unresponsive to conventional therapies, ECMO is required. While the surgical repair is relatively simple, determining the optimal timing for surgery in patients requiring ECMO is particularly challenging. This review explores the dilemma of surgical timing and proposes a two-staged approach: a reduction in herniated organs and the creation of a silo to relieve abdominal pressure before initiating ECMO, with defect closure following ECMO decannulation. Recent Findings: Studies support pre-, on-, and post-ECMO repair, each with its own risks and benefits. Pre-ECMO repair may enhance ECMO efficacy by relieving organ compression but poses risks due to instability. Post-ECMO repair is safer but may result in losing the chance to repair. On-ECMO repair has significant hemorrhage risks, but early repair with careful anticoagulation management is currently recommended. Recently, the author reported a successful case using a two-staged approach-reducing herniated organs and creating a silo before ECMO, followed by defect closure after ECMO decannulation-which suggests a potential alternative strategy for managing severe CDH. Summary: A two-staged approach may offer a solution for severe CDH patients requiring ECMO.